2016
DOI: 10.17511/ijpr.2016.i07.06
|View full text |Cite
|
Sign up to set email alerts
|

Use of NESTROFT as a screening test for the carriers of thalassemia major

Abstract: Objective: To evaluate the utility of NESTROFT as a screening test for carriers of thalassemia major. Design: prospective study. Settings and participants: Total 121 clinically normal siblings, of thalassemia major patients who are registered at thalassemia welfare society of J K LON hospital Kota, were selected randomly for study. Intervention: All cases were investigated for CBC, Mentzer's index, NESTROFT and HbA2 estimation by HPLC method. Result: Total 121 cases were screened for thalassemia carrier by HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For field research and mass screening, NESTROFT has proven to be an effective, efficient, quick, and reasonably priced tool. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For field research and mass screening, NESTROFT has proven to be an effective, efficient, quick, and reasonably priced tool. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…A study done in tertiary care hospitals showed 100% sensitivity, 100% specificity, 100% PPV, and 100% NPV. [ 15 ] The results have the highest values because the study is hospital-based. A study done in the year 2021 showed similar results: a sensitivity of 84.2%, a specificity of 96.2%, a PPV of 69.5%, and an NPV of 98.3%.…”
Section: Discussionmentioning
confidence: 99%